How impactful is G2P in driving account activity? Indian evidence - Saibal Ghosh (Journal of Open Innovation: Technology, Market and Complexity)
The usefulness of G2P payments for supporting account activity as part of financial inclusion has been well-recognised in the literature. However, not much empirical evidence is available to support this contention. To inform the debate, the study uses repeated cross-sectional survey data for India at the district level to analyse the role of G2P payments on account activity. Using appropriate empirical design to account for sample selection bias, we find that G2P payments increase account activity by anywhere between 45 and 70 percentage points, with the magnitudes being higher when such credits are made directly into bank accounts than when they are paid in cash. Among others, income, education, gender and marital status appear to positively impact the use of bank accounts. We employ several robustness tests and continue to find evidence supporting these findings.